(untitled) (Globalization and Business, 2023)
Assessing the impact of the COVID-19 crisis on societies, economies and vulnerable groups is fundamental to inform and tailor the responses of governments and partners to recover from the crisis and ensure that no one is left behind in this effort. The world is facing the dangers posed by the global spread of the new COVID-19 which has created new set of problems for the economy. The Crisis has caused many difficulties for Georgia and its economy. The impact of the new virus is rippling through Georgian economy, but it might take a few months to fully see the fallout in data that track economic performance in Georgia. The coronavirus pandemic is putting enormous pressure on healthcare systems, it is affecting the global economy in an unprecedented way and it is leading to a downturn incomparable to any other economic crisis in recent history. It is hard to estimate the depth and duration of the recession for every region and country. It will depend not only on the development of pandemic, but also on specific economic futures, strengths and vulnerabilities. Today the economy is a hostage to medicine. In Georgia, had on the following industries: tourism, transportation, agriculture and real estate had the biggest negative impact from COVID-19. Hotels, restaurants and tourist agencies demand from the government to postpone the budget taxes and bank loans. Meanwhile the hospitality sector of Georgia tries to minimize the cost because of sharp drop in revenue. Different countries will need different responses to dealing with the global economic challenges. As a fact COVID-19 has taught many countries to survive during the crisis period. From the economic stand point of view, every country has suffered the negative consequences of the COVID-19. The level of the consequences had direct correlation on the economic factors.